When Fatherhood, Masculinities, and Structural Factors Collide: Fatherhood and its Complexities (Social Science Review, 2023)
This research intends to explore the complex dynamics between fatherhood and masculinities, and how these dynamics are shaped by different structural factors, which hinder the enactment of involved fatherhood in two generations of Bangladeshi fathers. It accumulates the voices and experiences of older and younger fathers living in Dhaka, Bangladesh. The findings demonstrate how the construction of fatherhood is influenced by Connell’s (1987) “hegemonic masculinity” ideology, where specific male identities – protectors and providers – are valued, at the cost of not performing involved or compassionate fatherhood. In addition, this study illustrates how the social expectations create pressure for men to fit in the prescribed categories; although, an attention is given towards the fluidity of hegemonic masculinity, and the challenges it faces from both generations’ fathers with the changing norms, and due to the practice of alternative masculinities – mostly by the young fathers. This research follows qualitative research methodology employing in-depth interviews and Focus Group Discussions (FGDs) to have a deeper insight of what happens when structural factors, masculinity and fatherhood collide. The study concludes that both generations fathers are opening towards involved fatherhood, yet traditional fatherhood still dominates the domestic spheres.Social Science Review, Vol. 39(3), Dec 2022 Page 113-131